2007
DOI: 10.1080/09637480601108307
|View full text |Cite
|
Sign up to set email alerts
|

The effects of essential oils and aqueous tea infusions of oregano (Origanum vulgareL. spp.hirtum), thyme (Thymus vulgarisL.) and wild thyme (Thymus serpyllumL.) on the copper-induced oxidation of human low-density lipoproteins

Abstract: In this study, the antioxidative capacity effect of essential oils and aqueous tea infusions obtained from oregano, thyme and wild thyme on the oxidation susceptibility of low-density lipoproteins (LDL) has been studied. The results indicate a dose-dependent protective effect of the tested essential oils and aqueous tea infusions on the copper-induced LDL oxidation. The protective effect of essential oils is assigned to the presence of phenolic monoterpenes, thymol and carvacrol, which are identified as the do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 12 publications
2
37
0
6
Order By: Relevance
“…The major aqueous constituents of oregano are rosmarinic acid, eriocitrin, luteolin-7-oglucoside, apigenin-7-O-glucoside, origanol A and B, and ursolic acid (Sheibani et al, 2010). Rosmarinic acid and origanol A and B, which are the most abundant components of the aqueous extract of oregano, have antioxidative activities (Kulisic et al, 2007;Matsuura et al, 2003). Previous studies have reported that the essential oil of O. vulgare has antioxidant capacity, which has been linked to components such as thymol, carvacrol, d-terpinene, and p-cymene (Halici et al, 2005;Odabasoglu et al, 2004;Russo et al, 2002).…”
Section: Cyclophosphamidementioning
confidence: 99%
“…The major aqueous constituents of oregano are rosmarinic acid, eriocitrin, luteolin-7-oglucoside, apigenin-7-O-glucoside, origanol A and B, and ursolic acid (Sheibani et al, 2010). Rosmarinic acid and origanol A and B, which are the most abundant components of the aqueous extract of oregano, have antioxidative activities (Kulisic et al, 2007;Matsuura et al, 2003). Previous studies have reported that the essential oil of O. vulgare has antioxidant capacity, which has been linked to components such as thymol, carvacrol, d-terpinene, and p-cymene (Halici et al, 2005;Odabasoglu et al, 2004;Russo et al, 2002).…”
Section: Cyclophosphamidementioning
confidence: 99%
“…Caffeic acid and gallic acid are naturally found in the majority of herbs and are present in the free form or commonly bound as esters, depsides, and/or glycosides. Rosmarinic acid is a typical active compound of sage, marjoram, oregano and other herbs; (+)-catechin is free or as an ester mainly with gallic acid (Ziaková & Brandšteterová 2003;Yanishlieva et al 2006;Kivilompolo & Hyötyläinen 2007;Kulisic et al 2007;Velíšek 2009 etc. ).…”
Section: Determination Of Antioxidant Capacity Of Extractsmentioning
confidence: 99%
“…Carvacrol minimizes oxidation of the lipid components in foods and can serve as a natural replacement of synthetic antioxidative food additives [11]. EOs and aqueous tea infusions obtained from oregano, thyme and wild thyme prevent oxidation of LDL that transport dangerous cholesterol and triglycerides from the liver to peripheral tissues [12]. Jukic et al [13] found that thymol, carvacrol and their derivatives exhibited a strong inhibitory effect on acetylcholinesterase (AChE), an enzyme that degrades the neurotransmitter acetylcholine.…”
mentioning
confidence: 99%